A critical review of career research and assistance through the cultural lens: towards cultural praxis of athletes' careers - Stambulova, N. B.; Ryba, T. V. (International Review of Sport and Exercise Psychology, 2014)
In this review article, a content area of athlete career in sport psychology is analyzed through the cultural lens: that is, through paradigmatic perspectives of cross-cultural psychology, cultural psychology, and cultural studies. Based on previous review papers, but mainly on the chapters of the anthology Athletes' Careers across Cultures, we identified three dominant (North American, Australian, and European) and two emerging (Asian and South American) cultural discourses in the career topic. These discourses are characterized by research foci, theoretical frameworks, and career assistance programs in action. Our critical analysis of career research and assistance around the world further indicates a need for more contextualized and culturally competent career projects, which blend theory/research, applied work, and lived culture into cultural praxis. To satisfy this need, a new paradigm termed cultural praxis of athletes' careers is suggested. In conclusion, we emphasize the importance of review papers in negotiating emerging terminology, values, principles, and approaches underlying the career topic, and share some ideas for future reviews in career research and assistance.